2020
DOI: 10.1177/1010428320933512
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling of microRNA target genes in colorectal cancer

Abstract: Colorectal cancer is the second and third most common cancer in men and women, respectively, worldwide. Alterations such as genetic and epigenetic are common in colorectal cancer and are the basis of tumor formation. The exploration of the molecular basis of colorectal cancer can drive a better understanding of the disease as well as guide the prognosis, therapeutics, and disease management. This study is aimed at investigating the genetic mutation profile of five candidate microRNAs (hsa-miR-513b-3p, hsa-miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The process of carcinogenesis and therapeutic responses present a terrific challenge to favorable therapeutic outcome [41]. However, identifying cancer specific targets can pave the way for effective treatment options against specific cancer types [42]. Computational approaches are extensively used to investigate molecular and genetic mechanism of cancer progression by identifying lead genes and the abnormal regulatory pathways of disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…The process of carcinogenesis and therapeutic responses present a terrific challenge to favorable therapeutic outcome [41]. However, identifying cancer specific targets can pave the way for effective treatment options against specific cancer types [42]. Computational approaches are extensively used to investigate molecular and genetic mechanism of cancer progression by identifying lead genes and the abnormal regulatory pathways of disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, colorectal cancer (CRC) is a foremost contributor to cancer-related death annually and continues to pose a significant challenge to the world [ 1 ]. With reports of greater than 1.8 million new cases of CRC diagnoses and approximately 0.86 million deaths throughout the globe in 2018 [ 2 ], CRC is the third most frequently occurring cancer, and the third most common cause of cancer-associated deaths in both genders [ 3 ], representing 10% of all cancer diagnosed yearly [ 4 ]. Over the past decade, increasing evidence points to the role of G-protein activating subunit gene mutations in the development of tumours, i.e., CRC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins, including those that are produced by the genes GNAS, GNAQ, GNA11 and GNA12 bind to G-protein-coupled receptors (GPCRs) and are essential for the transduction of cellular signals. The process for the initiation and progression of CRC stems from the accumulation of several aberrant genetic and epigenetic alterations in the epithelium cells of the colon and rectum [ 2 ]. Reports on overexpression of the GNAS gene in cancers and, linked with tumourigenesis metastasis and progression are vast [ 2 ]; however, the detailed understanding of the genetic contribution of GNAS mutation in colorectal cancer (CRC) progression remains ambiguous and unclear [ 2 , 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is urgent to find new therapeutic methods and develop effective biomarkers for the early diagnosis, treatment, and prognosis assessment of colorectal cancer to improve the survival status. Some studies have demonstrated that epigenetic mechanisms play a key role in cancer progression, particularly non-coding RNAs (ncRNAs) [ 9 ]. Indeed, many studies have demonstrated that the development pathogenesis of colorectal cancer is highly influenced by ncRNAs [ 10 ], the abnormal expression of oncogenic and tumor-suppressor molecules, and the abnormal activation of various cell signaling pathways [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%